Internalisasi Nilai-Nilai Aswaja dalam Konten Dakwah Digital : Analisis Konten TikTok dan YouTube Perspektif Islam Nusantara - Anis Dwi Arini; Ganjar Gandara; Indriana Muliyanti; Prio Rionggo; Ujang Toyib Taopik; Yadi Ruslan; Imam Asrofi (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
The development of digital media has created new spaces for Islamic preaching practices, particularly through social media platforms such as TikTok and YouTube. Amid the proliferation of religious content that may trigger social polarization, preaching based on Ahlussunnah wal Jama’ah (Aswaja) values plays a crucial role in strengthening religious moderation. This study aims to analyze the internalization of Aswaja values tawassuth (moderation), tasamuh (tolerance), and tawazun (balance) in digital da’wah content on TikTok and YouTube from the perspective of Islam Nusantara. This research employs a qualitative approach using content analysis of selected da’wah videos chosen through purposive sampling. The findings indicate that Aswaja values are internalized contextually and adaptively according to the characteristics of each platform. TikTok functions as an effective medium for delivering concise and persuasive messages, particularly related to tolerance and religious moderation, while YouTube serves as a space for deeper, more argumentative, and reflective Islamic discourse. These findings affirm that Aswaja based digital da’wah within the framework of Islam Nusantara plays a strategic role in promoting religious moderation and maintaining social harmony in a plural digital society.